Memory retention for multilingual note taking platform / Chandra Latha Ramachandran - Chandra Latha , Ramachandran (2021)
Technology developments such as laptop, smartphone, and video lectures are altering pedagogy dynamics and influencing the way students compose and review notes. Confused on how to learn effectively have led to a lot of trial and error on the note taking methods between students. This study explore the effect of memorization retention using the pen, the laptop, and the smartphone on multilingual note taking which is in Malay (Jawi Script), English (Latin Script), Chinese (Hanzi script) and Tamil (Tamil script). A model of note taking is designed to assist in the development of an effective learning platform. A progressive web application (PWA) named MemRetz for mobile and laptops respectively were developed based on the designed model. During this analysis, about thirty participants for each language are given a group of articles and video in three different mediums that consists of various lengths of characters for each article and duration for each video. The note taken, medium used and memory retention score (percentage of correctness × time taken to complete the test) are recorded and measured to determine the effect of memorization retention using different mediums. Results proved that note taking does influence memory retention. However, different scripted language or medium used do not have an effect on memory retention score. Study’s results suggest that students may read article and take notes using any language or medium they prefer and comfortable with as it does not affect the memory retention. The usage of note-taking software in an E-learning platform is useful since it increases participants' ability to take notes and helps them remember.